Landscape connectivity analysis and proposition of the main corridor network for the jaguar in South America - JĘDrzejewski, WŁOdzimierz (2023)
Large parts of the formerly continuous jaguar Panthera onca range have been lost or fragmented. We performed an analysis with Linkage Mapper to evaluate connectivity between all 92 patches of the 2020 jaguar range in South America. We used two Linkage Mapper tools: (1) the Linkage Paths to calculate the cost-distance values and to select least-cost paths as potential corridors for jaguar movements and (2) the Barrier Mapper to identify barriers along the potential corridors. We derived land-scape resistance values necessary for this analysis from the probabilities of jaguar occurrence estimated with species distribution models. Our analysis indicates that connectivity for jaguars is still good within the central Amazonian and Guiana Shield portions of the jaguar’s range. However, outside of this central core, connectivity between the fragmented jaguar populations is generally poor, e.g. in the Andes, Llanos, Atlantic Forest, Caatinga, and Cerrado. Barrier sections cover 21% of the area of potential corridors, and high resistance values were found on 30% of the corridor area. This situation is worsened by high road density around most barrier sections of the potential corridors. The Chocó region of north-western Colombia is likely isolated from the rest of the jaguar range in South America, which means that jaguar populations of Central America have no or minimal connections with the Amazonian populations. Similarly, the connectivity between fragmented jaguar populations in eastern South America (Caatinga, Cerrado, and Atlantic Forest eco-regions) is disrupted at several potential corridors, although some corridors of this region may still retain some potential to facilitate jaguar movement. Only 9% of the area of potential corridors are located within protected areas. Our results can guide planning for jaguar conservation action on a large spatial scale and help focus on sites where such efforts can be most effective and are most needed.